1970
DOI: 10.1002/zamm.19700501006
|View full text |Cite
|
Sign up to set email alerts
|

Transition Analysis of Collapse of Thick Cylinders

Abstract: Hive einiger ad-hoc-Annahmen wie derjenigen der Inkompressibilitat und einer besonderen Form der FlieJbedingung hat T . Y . T h o m a s theoretische Ergebnisse uber den Zusammenbruch dicker Zylinder erhulten, die mit den experimentellen Ergebnissen von P . W. B r i d g m a n gut iibereinstimmen. Die von B . R . Seth und anderen aufgestellte Ubertragungstheorie liefert bereits diese und noch allgemeinere Ergebnisse, ohne irgendwelche Annahmen machen zu mussen. By making a number of ad-hoc assumptions like that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1974
1974
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…A thick-walled cylinder is also widely used as a structural component in oil refineries, power industries, atomic power plants, etc. Problems of thickwalled cylinder under internal pressure have been analysed [1][2][3][4] for isotropic homogeneous elastic-plastic states. In their treatment, the following assumptions were made: (i) the incompressibility conditions, (ii) the deformation is small enough to make infinitesimal strain theory applicable,and (iii) the yield criterion, Incompressibility of the material in plasticity is one of the most important assumption that simplifies the problem.…”
Section: Elastic-plastic Transition Of Transversely Isotropic Thick-wmentioning
confidence: 99%
See 2 more Smart Citations
“…A thick-walled cylinder is also widely used as a structural component in oil refineries, power industries, atomic power plants, etc. Problems of thickwalled cylinder under internal pressure have been analysed [1][2][3][4] for isotropic homogeneous elastic-plastic states. In their treatment, the following assumptions were made: (i) the incompressibility conditions, (ii) the deformation is small enough to make infinitesimal strain theory applicable,and (iii) the yield criterion, Incompressibility of the material in plasticity is one of the most important assumption that simplifies the problem.…”
Section: Elastic-plastic Transition Of Transversely Isotropic Thick-wmentioning
confidence: 99%
“…Infact, in most of the cases, it is not possible to find a solution in closed form without this assumption. Transition theory 4 does not require any of the above assumptions, and thus solves a more general problem. This theory utilizes the concept of generalised strain measure, which not only gives the well-known strain measures, but can also be used to find the stresses in plasticity and creep problems by determining the asymptotic solution at the transition points of the governing differential equations.…”
Section: Elastic-plastic Transition Of Transversely Isotropic Thick-wmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that for the uni-axial case a generalized measure, which includes all the known measures of Cauchy, Green, Almansi, Hencky and others, is given by [7]. The generalized principal strain measure is defined as [8] …”
Section: Introductionmentioning
confidence: 99%
“…where n is the strain measure coefficient, e ii A is the Almansi finite strain component, i = 1 , 2 , 3 , and n = 2 , 1 , 0 , 1 , 2 , respectively, indicate Green, Cauchy, Hencky, Swainger, and Almansi measures. This theory has been applied to a more general and wider range of problems [1926]. Using his theory, Seth [25] studied elastic–plastic transition stresses and strains in tubes under pressure.…”
Section: Introductionmentioning
confidence: 99%